2019
DOI: 10.3329/bjp.v14i2.40098
|View full text |Cite
|
Sign up to set email alerts
|

Solanum incanum extract enhances wound healing and tissue regeneration in burn mice model

Abstract: This study was conducted to evaluate the topical efficacy of Solanum incanum for the treatment of partial-thickness burn in mice model. Mice were treated with topical ointment of S. incanum three times daily for 14 days. The wound healing was observed through wound contraction and histological parameters. The group treated with S. incanum ointment showed 81% reduction in wound area as compared to negative control where wound area reduced to 22%. The histological analysis further confirmed that ointment favors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Step 8: The study of mesenchymal progenitors content in the wound, their functional activity, and production of growth factors by stromal cells from the surface of the wound. Goldberg et al, 2006;Zyuz'kov et al, 2012 Reference (video) Öz et al, 2016;Qureshi et al, 2019 Liability Company Assortiment Firm, Sergiev Posad city, Russia), water ad libitum. To exclude seasonal fluctuations of studied parameters, all the experiments were performed in the autumn-winter period.…”
Section: Methodsmentioning
confidence: 99%
“…Step 8: The study of mesenchymal progenitors content in the wound, their functional activity, and production of growth factors by stromal cells from the surface of the wound. Goldberg et al, 2006;Zyuz'kov et al, 2012 Reference (video) Öz et al, 2016;Qureshi et al, 2019 Liability Company Assortiment Firm, Sergiev Posad city, Russia), water ad libitum. To exclude seasonal fluctuations of studied parameters, all the experiments were performed in the autumn-winter period.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive research has demonstrated the broadspectrum antibacterial activity of Melia azedarach, as evidenced by its inhibitory effects against Proteus mirabilis, Enterobacter aerogenes, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, and Bacillus subtilis (Abbas et al, 2017;Zahoor et al, 2015). Solanum incanum extracts have also exhibited notable bactericidal and nematicidal properties (Anwar, 2018), complemented by their traditional use in wound healing, pain relief, and treatment of protozoan infections (Mwonjoria et al, 2014;Qureshi et al, 2019;Waweru et al, 2017). These observations underscore the potential therapeutic value of these plant extracts in addressing drug-resistant bacterial infections and inspire further investigation into their antimicrobial mechanisms and potential applications in modern medicine.…”
Section: Introductionmentioning
confidence: 94%
“…Other medicinal uses include relieving pain in patients with menstruation, liver disease, onchocerciasis, pleurisy, pneumonia, and rheumatism [ 14 ]. Other plant parts are also commonly used to treat a wide range of dermatological problems, including ringworm, burns, sores, rashes, wounds, warts, carbuncles, inflammations, and benign tumors [ 15 ]. In the Libo Kemkem district, in the Amhara region of Ethiopia, it is claimed that the root part chewed and then taken as a juice has been used to treat diabetes mellitus [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous experimental studies that proved various parts of the plant have a variety of activities, including in vitro antimicrobial activity of the leaf, fruit, and stem extract [ 16 ]; analgesic and spasmolytic activity of the leaf extract [ 17 ]; anti-inflammatory and antinociceptive effects of the root extract [ 14 ]; antihyperlipidemic effect of the fruit extract [ 18 ]; in vitro antiprotozoal activity of the leaf extract [ 19 ]; wound healing and anti-inflammatory activity of the leaf extract [ 15 ]; and antischistosomal activity of the root extract [ 20 ].…”
Section: Introductionmentioning
confidence: 99%